KEEFEKTIFAN TIGA JENIS INSEKTISIDA NABATI TERHADAP KUTU PUTIH PEPAYA PARACOCCUS MARGINATUS DAN KEAMANANNYA TERHADAP LARVA KUMBANG PREDATOR CURINUS COERULEUS - Ahmad Sifa; Djoko Prijono; Aunu Rauf (Universitas Lampung, 2013)
Effectiveness of three botanical insecticides against the papaya mealybug Paracoccus marginatus and their safety to the predatory Curinus coeruleus larvae. Preparations of Tephrosia vogelii (Tv) leaf extract (0.5% and 1% w/v), Annona squamosa (As) seed extract (0.5% and 1%), and Cinnamomum multiforum (Cm) leaf essential oil (1% and 2%), and their mixtures (Mix-1: Tv 0.25% + As 0.25% + Cm 0.5%; Mix-2: Tv 0.5% + As 0.5% + Cm 1%) were tested for their effectiveness on third-instar nymphs of Paracoccus marginatus by spraying the test materials on undetached papaya leaves and by direct spraying on the test insects using Potter spray tower. Tv extract was also applied on the test insects placed on undetached papaya leaves. The safety test was done by direct spraying of the test materials on the predatory Curinus coeruleus larvae using Potter spray tower. Tv and As extracts at a concentration of 1% each are potential to be used for the control of P. marginatus. Spraying of T. vogelii extract on the test P. marginatus nymphs placed on papaya leaves was more effective than spraying of the test materials on papaya leaves or direct spraying on the test insects only. The treatment with Cm essential oil required twice the concentration of Tv and As extracts to obtain the same level of effectiveness. The treatment with Mix-2 caused lower P. marginatus mortality than the sum of mortality caused by its components applied separately. Nonetheless, the three botanical insecticides and their mixtures were safe to C. coeruleus larvae. On the other hand, although the synthetic insecticide imidacloprid (neonicotinoid), included in the study for comparison, was effective against P. marginatus, it was also toxic to the predatory C. coeruleus larvae so its use should be avoided or limited.